2015
DOI: 10.1017/cem.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a point-of-care ultrasound protocol on the diagnostic performance of medical learners during simulated cardiorespiratory scenarios

Abstract: Background: Goal-directed point-of-care ultrasound (PoCUS) protocols have been shown to improve the diagnostic accuracy of the initial clinical assessment of the critically ill patient. The diagnostic impact of the Abdominal and Cardiac Evaluation with Sonography in Shock (ACES) protocol was assessed in simulated emergency medical scenarios. Methods: Following a focused PoCUS training program, the diagnostic accuracy, confidence, and precision of 12 medical learners participating in standardized scenarios were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
(10 reference statements)
1
22
0
Order By: Relevance
“…A number of previous studies employed training curricula for medical students on ultrasonography protocols [37][38][39]. Four other studies used a point-of-care ultrasonography training program to determine diagnostic performance in various clinical scenarios [36,[40][41][42]. All studies showed feasibility to train medical students to perform ultrasonography after a relatively short amount of training, which is comparable to the training medical students received in our study.…”
Section: Discussionsupporting
confidence: 74%
“…A number of previous studies employed training curricula for medical students on ultrasonography protocols [37][38][39]. Four other studies used a point-of-care ultrasonography training program to determine diagnostic performance in various clinical scenarios [36,[40][41][42]. All studies showed feasibility to train medical students to perform ultrasonography after a relatively short amount of training, which is comparable to the training medical students received in our study.…”
Section: Discussionsupporting
confidence: 74%
“…In these nine studies evaluating medical students' diagnostic accuracy with POCUS, relatively few students were trained and evaluated (sample sizes ranged from 2 to 30 subjects, with a median of 10). Trained medical students performed POCUS with acceptably proficient accuracy compared with the diagnostic standard . Medical students' diagnostic accuracy using ultrasound was found to be superior to that of the clinical evaluation of attending physicians in the two studies evaluating this outcome .…”
Section: Resultsmentioning
confidence: 88%
“…Trained medical students performed POCUS with acceptably proficient accuracy compared with the diagnostic standard. 10,[70][71][72] Medical students' diagnostic accuracy using ultrasound was found to be superior to that of the clinical evaluation of attending physicians in the two studies evaluating this outcome. 36,55 Results were mixed for the incremental benefit outcome; whereas one study reported significant improvement in diagnostic accuracy with the addition of POCUS, 73 rates of accurate diagnosis of some conditions were not always improved by the addition of ultrasound (e.g.…”
Section: Rationale 3: Ultrasound Improves Medical Students' Diagnostimentioning
confidence: 99%
“…Following the sessions, students completed an anonymous 5-point Likert questionnaire. The 5-point Likert scale ranged from not confident [1] to very confident [5] and assessed students' confidence in the following competency domains: ▪ Ability to identify major abdominal organs using hands-on wireless ultrasound scanners ▪ Physical examination skills after the hands-on ultrasound sessions…”
Section: Assessment Of Student Confidencementioning
confidence: 99%